Load frequency control for power systems with increasing penetration of renewable energy sources (part I) - Chen, XiaoYu (Nanyang Technological University, 2022)
In power system, frequency stability is one of the most critical topics and it plays an important role in power quality. Due to the increase in the interconnection of a power system and penetration of renewable energy sources, the loads are varying dynamically. When the load suddenly changes, the power exchanged between the systems may deviate and the frequency of the system may fluctuate. Hence, load frequency control becomes more and more necessary in power system. It refers to the ability of the system to maintain or recover a stable frequency when the power system is subjected to small or large disturbances that causes imbalance between generation and load power. With the rapid development of the world, the demand for energy in each country is also increasing. Energy can be divided into non-renewable energy and renewable energy. Non-renewable energy mainly includes coal, oil, natural gas, chemical energy and nuclear fuel. Renewable energy mainly includes wind, hydro, ocean, tidal, solar and biomass energy. As we all know, non-renewable energy will pollute and destroy the environment. Meanwhile, they are limited which will lead to energy depletion. Therefore, renewable energy will be the trend of future development. This project will study the functions of load frequency control and set up models of load frequency control of a power system with penetration of renewable energy source. At the same time, design control scheme to improve the system performance. All the above mentioned will be simulated by using MATLAB-Simulink. It mainly achieves for the two-area interconnected system with wind power.